(untitled) (Cardiovascular Journal, 2023)
This is a challenging case of Wolff–Parkinson–White syndrome which was located in the right posteroseptum region. Patient had a previous unsuccessful attempt at ablation. It is often difficult to precisely locate this type of accessory pathway. A repeat procedure using 3D electroanatomic mapping, the electroanatomic geometry of the heart was created. The accessory pathway potential was identified and the accessory pathway was successfully ablated in minimum amount of time. In this case report showed that the advanced three-dimensional cardiac mapping system plays a very important role in guiding clinicians in order to precisely locate and safely ablate this type of challenging accessory pathway. Cardiovasc j 2023; 16(1): 47-52